A virtual element method for frictional contact including large deformations. Issue 7 (12th August 2019) - Wriggers, Peter; Rust, Wilhelm T.
Abstract : Purpose: This paper aims to describe the application of the virtual element method (VEM) to contact problems between elastic bodies. Design/methodology/approach: Polygonal elements with arbitrary shape allow a stable node-to-node contact enforcement. By adaptively adjusting the polygonal mesh, this methodology is extended to problems undergoing large frictional sliding. Findings: The virtual element is well suited for large deformation contact problems. The issue of element stability for this specific application is discussed, and the capability of the method is demonstrated by means of numerical examples. Originality/value: This work is completely new as this is the first time, as per the authors' knowledge, the VEM is applied to large deformation contact.